Optimizing approach of water allocation to off takes during reduced flows - Shaikh, Irfan Ahmed; Wayayok, Aimrun; Mangrio, Munir Ahmed; Alhussain, Ziyad Ali; Chandio, Farman Ali; Ahmed Khan, Zaheer; Asghar Khan, Waseem; Mohammed, Mogtaba; Elbashir, Murtada K.; Rahman, Jamshaid Ul (Springer, 2022)
Multi-objective optimization models with an index were developed based on farmers’ preferences, local requirements, supplies available at the head of the canal, system losses, crop demand about different growth stages, and field soil moisture balance. The models were applied using linear programming. The Model 1 determines the cropping pattern by maximizing net economic benefits using a monthly basis lumped volume available at the head of the canal and is set to the minimum and maximum area constraints along with the constraint of minimum main crop area. The areas for different crops given by the first model form input for the Model 2. The other inputs of Model 2 included periodic supply available at the head of the primary canal (7-day period in this study), root growth depth, demand, and soil moisture constants. The Model 2 optimizes the sum of relative yields of all the crops and provide the irrigation levels of various crops for specified periods. Finally, the distributed area and irrigation levels determined by Model 2 are used in conjunction with the losses to decide flow rates of off takes. The complete program was implemented in the West branch irrigated area of Mirpurkhas subdivision. The results showed that the resources were allocated to off-takes in a competitive and conflict-free manner.